Pemanfaatan Teknologi Artificial Intelligence dalam Efektifitas Pembelajaran Mahasiswa - Michella Christy Tania Supit; Shelty Deity Meity Sumual (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to describe the use of Artificial Intelligence (AI) technology to improve the learning effectiveness of students at Samawa University. The study used a descriptive quantitative approach to obtain an objective picture of the level of understanding, use, benefits, and challenges of AI in the learning process. The study subjects consisted of 67 students who had utilized AI in academic activities. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics in the form of percentages and frequency distributions. The results showed that the majority of students had a high level of understanding and use of AI. AI was perceived as significantly assisting students in understanding course material and increasing learning effectiveness through easy access to information, efficient study time, and support for independent learning. Furthermore, the benefits of AI use were deemed to outweigh the challenges faced, although challenges related to ethical use and potential dependency persist. Lecturer and institutional support for AI utilization was also positive and played a significant role in encouraging the productive and responsible use of AI. Overall, this study demonstrates that Artificial Intelligence technology has significant potential as an effective learning support medium, with the caveat that mentoring and digital literacy are needed to ensure its use remains aligned with academic principles.